Динамические характеристики робастной системы управления синхронными приводами прокатных станов с учетом их взаимосвязи через прокатываемый металл - Кузнецов, Борис Иванович; Волошко, Александр Валерьевич; Бовдуй, Игорь Валентинович; Виниченко, Елена Владимировна (НТУ "ХПИ", 2010)
Разработан метод робастного управления синхронными главными приводами прокатных станов с учетом нелинейных моментов трения между валками взаимным влиянием прокатных валков друг на друга в ходе прокатки через прокатываемый металл. Приведен пример динамических характеристик синтезированной системы.

The method of robust control synthesis by main drives of flatting mills as a two mass electro mechanics system for a short line and as a three mass one for the long line are developed taking into account the resilient elements in transmissions boundary path by the executive motors, reducing gears and rental felling, friction nonlinear moments between felling by the mutual influencing of rental rollers on each other during rolling through the rolled metal. Examples of dynamic characteristics of such systems are given.
Dynamic characteristics of robust control system by rolling mills main drives with related through the rolled metal as robust control system plant
Keywords: главные приводы; частотные преобразователи; динамические нагрузки; режим буксования валков; rolling mills; main drives; robust control system